Comorbidity between Klinefelter syndrome and diaphragmatic hernia. A case report - Valdez, Carolina Melendez; Altmayer, Stephan Philip Leonhardt; Faria, Adyr Eduardo Virmond; Weiss, Aline; Telles, Jorge Alberto Bianchi; Fell, Paulo Renato Krall; Targa, Luciano Vieira; Zen, Paulo Ricardo Gazzola; Rosa, Rafael Fabiano Machado (São Paulo Medical Journal, 2014)
CONTEXT: Intrathoracic cystic lesions have been diagnosed in a wide variety of age groups, and the increasing use of prenatal imaging studies has allowed detection of these defects even in utero. CASE REPORT: A 17-year-old pregnant woman in her second gestation, at 23 weeks of pregnancy, presented an ultrasound with evidence of a cystic anechoic image in the fetal left hemithorax. A morphological ultrasound examination performed at the hospital found that this cystic image measured 3.7 cm x 2.1 cm x 1.6 cm. Polyhydramnios was also present. At this time, the hypothesis of cystic adenomatoid malformation was raised. Fetal echocardiography showed only a dextroposed heart. Fetal magnetic resonance imaging produced an image compatible with a left diaphragmatic hernia containing the stomach and at least the first and second portions of the duodenum, left lobe of the liver, spleen, small intestine segments and portions of the colon. The stomach was greatly distended and the heart was shifted to the right. There was severe volume reduction of the left lung. Fetal karyotyping showed the chromosomal constitution of 47,XXY, compatible with Klinefelter syndrome. In our review of the literature, we found only one case of association between Klinefelter syndrome and diaphragmatic hernia. CONCLUSIONS: We believe that the association observed in this case was merely coincidental, since both conditions are relatively common. The chance of both events occurring simultaneously is estimated to be 1 in 1.5 million births.